OP0195 What is the impact of juvenile idiopathic arthritis in adulthood? the monocentric experience of 240 patients followed in a transition tertiary clinic of rheumatology. (15th June 2017) - Pontikaki, I; Argolini, LM; Artusi, C; Meroni, PL
Abstract : Background: There are many differences in clinical manifestations, assessment and management of Juvenile Idiopathic Arthritis (JIA) between childhood and adults' arthritis onset. The transition from pediatric to the adult care emphasizes a lot of aspects that need to be addressed. Objectives: To describe the long-term outcome of JIA. Methods: Two-hundred and forty patients affected by JIA and referred to a transition care rheumatology tertiary centre were considered between 1999 and 2016. The outcome assessment included disease activity, medications, number of prosthesis implantation, pregnancy, mortality, social integration (mobility, employment status and educational level). Results: Seventy-four (30.8%) males and 166 (69.2%) females were included; 53 (22.1%) patients were lost in follow up. Subtypes of JIA at disease onset included 101 oligoarthirtis (42.1%), 67 polyarthritis (27.9%), 43 systemic arthritis (17.9%), 7 psoriatic arthritis (2.9%), 22 enthesitis related arthritis (9.2%). Forty-eight (20%) patients had persistent uveitis. Ninety-three implant prosthesis and 14 arthodesis were recordered. The average disease duration was 20 years, the median age of the patients was 27 (18–57) years. Five deaths (2.1%) occurred in this cohort. At follow up 117 (48.7%) had low active disease activity, 70 (29.2%) had moderate disease activity, 14 (5.8%) had a high disease activity, 24 (10%) were on remission ON medication and 15 (6.3%) OFF medication. Among patients still on medication, 59 (24.6%) were treated with oral steroids, 18 (7.5%) with csDMARDs and 169 (70.4%) with bDMARDs. Seventy-five (31.3%) patients had a higher educational level (university), 195 (81.3%) had an employment, 128 (53.3%) had a driving license. Twenty-one (8.8%) pregnancies were registered. The transition age was considered after age of sixteen years old. In this contest, it was important the multidisciplinary approach of each patient that was realized with the collaboration of other specialists (ophthalmologist, orthopedic, dermatologist, obstetric, psychologist). Conclusions: In the era of biologic therapy there was an important improvement in a lot variables of the long-term outcome of JIA. One-hundred-eighty-seven (77.9%) patients were still in tight control, not only because of the continuation of the biological therapy but also because of the multidisciplinary care carried out even during remission. JIA often persists over the adulthood. The long term follow up and care of these patients has to be conducted by a rheumatologist expertized in JIA in collaboration with other specialists. Disclosure of Interest: None declared